Oxygen Availability on the Application of Antimicrobial Photodynamic Therapy against Multi-Species Biofilms - Nie, Min; Yang, Jingmei; Rastelli, Alessandra Nara de Souza [UNESP]; Shen, Yuqin; Deng, Dongmei (MDPI, 2023)
Methylene blue (MB)- or Curcumin (Cur)-based photodynamic therapy (PDT) has been used as an adjunctive treatment for periodontitis. Its actual clinical efficacy is still in question because the lack of oxygen in a deep periodontal pocket might reduce the PDT efficacy. We aim to investigate the effect of oxygen on PDT efficacy and to examine if the addition of hydrogen peroxide (HP) could improve PDT performance anaerobically. To this end, we cultured 48 h saliva-derived multi-species biofilms and treated the biofilms with 25 µM MB or 40 µM Cur, HP (0.001%, 0.01% and 0.1%), light (L-450 nm or L-660 nm), or combinations thereof under ambient air or strictly anaerobic conditions. MB- and Cur-PDTs significantly reduced biofilm viability in air but not under anaerobic conditions. HP at 0.1% significantly enhanced the killing efficacies of both MB- and Cur-PDTs anaerobically. The killing efficacy of Cur-PDT combined with 0.1% HP was higher anaerobically than in air. However, this was not the case for MB-PDT combined with 0.1% HP. In conclusion, this study demonstrated that the biofilm killing efficacies of MB- and Cur-PDTs diminished when there was no oxygen. HP at 0.1% can enhance the efficacy of PDT performed anaerobically, but the level of enhancement is photosensitizer-dependent.
Keywords: biofilm; curcumin; methylene blue; oxygen; photodynamic therapy